INVESTIGETING THE EFFECTS OF STANDING TRAINING ON BODY FUNCTIONS AND ACTIVITY FOR NONAMBULATORY CHILDREN WITH MYELOMENINGOCELE (International Journal of Physiotherapy, 2017)
Background: It was indicated in many studies that verticalization have positive effects such as preventing fractures,regulating cardiopulmonary functions, increasing the head control, and the facilitation of postural muscles in pediatric patients, however, no study showing the effect of supported standing in patients with myelomeningocele on body functions and activity was encountered. The aim of this study is to examine the effects of structured supported standing training in children with myelomeningocele on body functions and activity according to ICF-CY.Methods: Twenty-five children with MMC aged between 3 and 17, who were divided into two groups-SST and control. The supported standing training was given to supported standing group 2 hours a day for 8 weeks in addition to the routine physical therapy program. Body functions were assessed with the Trunk Impairment Scale, and activity levels were assessed with the Gross Motor Function Measurement-88 and Pediatric Functional Independence Measurement at the beginning of the study, at the end of 8 weeks and at the end of 12 weeks from beginning.Results: The results of the structured supported standing training program during 8 weeks showed that children’s body functions and activity increased statistically significantly in SST group (p0.05).Conclusion: The results show that supported standing training effects the body functions and activity positively. It is recommended to educate the families for the supported standing training to be added to the routine physiotherapy and rehabilitation program for children with MMC and continue the training at home.